A dimensão pedagógica da pesquisa nos cursos de Biblioteconomia do Mercosul: reflexões sobre uma trajetória de harmonização curricular - Rodrigues, Mara Eliane Fonseca; Guimarães, José Augusto Chaves [UNESP] (Pontifícia Universidade Católica de Campinas, 2003)
Departing from the conception of research as a springboard to a good quality teaching, and from the fact that research constitutes an elected subject in the approved curricula for Mercosul's Library Studies courses, this paper analyses, from an historical point of view, the research conceptions developed during the Mercosul Meetings of the Library Studies' Program Administrators and Teachers _Encontros de Diretores e Docentes de Biblioteconomia (Porto Alegre, 1996; Buenos Aires, 1997; Santiago do Chile, 1998; Montevidéu, 2000; and Assunção, 2001). Such conceptions may be taken as subsidies for designing research policies for the Mercosul Library Studies undergraduate program. Therefore, besides the theoretical analysis of research articulated with teaching practices (especially in Library Studies education), this paper analyses the very development of the discussions related to the curriculum area 6 _Research-, that took place during the mentioned events.

Partindo da concepção de pesquisa como mola mestra para um ensino de qualidade e considerando-se o fato da mesma constituir uma das áreas curriculares acordadas para os cursos de Biblioteconomia do Mercosul, analisam-se, sob uma ótica histórica, as concepções de pesquisa desenvol-vidas no âmbito dos Encontros de Diretores e Docentes de Biblioteconomia do Mercosul (Porto Alegre, 1996; Buenos Aires, 1997; Santiago do Chile, 1998, Montevidéu, 2000 e Assunção, 2001) como subsídios ao delineamento de políticas de pesquisa para a graduação em Biblioteconomia no Mercosul. Com tal objetivo, este trabalho parte da reflexão teórica sobre pesquisa no ensino (em especial, no ensino de Biblioteconomia) para, a seguir, analisar a evolução das discussões da área curricular 6 _ Investigação _ levadas a cabo no âmbito dos referidos eventos.
The pedagogical dimension of the research in Mercosul's Library Studies courses: Reflections on a trajectory towards curricula harmonization
Keywords: pesquisa; ensino de Biblioteconomia; Mercosul; undergraduate program; research policies; curriculum; Library Studies; Mercosul